Temporal variation in small nonvolant mammal (Cricetidae and Didelphidae) microhabitat associations in the Upper Paraná Atlantic Forest - Owen, Robert (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
Many questions concerning habitat preferences of Neotropical small mammals remain unanswered. These questions include where the animal lives within and among the available habitats, and the temporal (seasonal and interannual) variation in the habitat associations. The objectives of this research were: (1) to determine the associations of non-volant small mammal species (Rodentia and Didelphimorphia) with specific microhabitat characteristics including vegetation structure in an area near the western boundary of the Upper Paraná Atlantic Forest, and (2) to evaluate seasonal and interannual variation in those associations. Three grids were sampled in three seasons (Dry, Wet, Variable) during two years (2015-2017). The four predominant small mammal species (Gracilinanus agilis, Akodon montensis, Hylaeamys megacephalus, and Oligoryzomys nigripes) were evaluated for seasonal and interannual variation in habitat preferences. Each of the four exhibited seasonal and/or interannual variation in microhabitat preferences for three to six of the 17 environmental variables analyzed. This is the first study to explicitly evaluate temporal variation in habitat associations of small mammals in the Atlantic Forest ecoregion. The temporal patterns of habitat association among these four predominant species reveal a complex spatially and temporally dynamic composition and structure in this small mammal community.
Keywords: El Niño; Environmental variables; Interannual variation; Paraguay; Seasonal variation; Vegetation structure